Network Meta-Analysis of Factors Influencing the Carbon Sink Capacity of Urban Park Green Spaces - Yutong JI; Tianyi LIN; Lian LIU; Xiong LI (Fengjing Yuanlin)
ObjectiveThis research mainly aims to identify the primary interactions between the factors influencing the carbon sink capacity of urban park green spaces and recognize the most effective landscape design strategies, thereby providing a foundational data set for the further development of a repository of lifecycle design strategies for urban green spaces. In light of the increasingly prominent role of urban green spaces in mitigating climate change, the research also seeks to highlight strategies that balance ecological functions with urban recreational and aesthetic needs.MethodThis research employs the network Meta-analysis method to explore the critical factors influencing the carbon sequestration potential of urban park green spaces, and conduct a systematic quantitative assessment of their respective carbon sink capacity. The research categorizes and statistically analyzes various factors currently involved in relevant research that affect the carbon sink capacity of urban park green spaces, whose interactions and cumulative impacts are assessed using the network Meta-analysis method. The Meta-analysis incorporates network evidence plots, league tables, and SUCRA (surface under the cumulative ranking curves) to evaluate the ranking and relative importance of different factors. Additionally, heterogeneity, bias, and errors are examined through subgroup analyses based on park scale (a), functional characteristics (b), and climatic conditions (c), accompanied by the evaluation of publication bias using funnel plots.ResultsThe analysis in this research involves 50 eligible literature articles published between 2000 and 2024, which are selected from a total of 952 articles initially collected. The research identifies 34 influencing factors, categorized into five distinct clusters: Design characteristics, habitat composition, planting strategies, maintenance methods, and external environment. The research results emphasize the multidimensionality of carbon sequestration in urban parks. Design characteristics and maintenance practices emerge as the most stable and broadly applicable factors. Their SUCRA values rank the highest, reflecting their consistent contribution to carbon sequestration across diverse settings. For instance, controlling the proportions of grasslands and pathways at 20% and 30%, respectively, and optimizing carbon storage while maintaining recreational value. Maintenance practices often act on other influencing factors to enhance carbon sink capacity, such as using native tree species, selecting natural materials, and designing low-maintenance sites to reduce the cost of maintenance. Habitat composition and planting strategies show significant influence under specific scenarios. Fast-growing tree species with large-canopy demonstrate strong initial carbon sink capacity, while subsequent maintenance, including pruning, is essential to sustain long-term benefits. Conversely, habitat composition reveals high heterogeneity, particularly influenced by tree density and vegetation diversity. Planting methods also hold significant importance in enhancing the carbon sequestration of urban parks, such as multi-layered vegetation structures that enhance carbon sink capacity but require careful adjustments to avoid excessive shading and competition, thereby achieving more efficient carbon sequestration. The influence of the external environment on carbon sink capacity is generally weaker but still requires attention in specific scenarios. The geographical location, climatic conditions, and soil types of different parks also lead to certain differences. Subgroup analysis by climate type shows that the research objects dominated by temperate climates show higher heterogeneity, presumably because the longitudinal differences of the research objects in temperate regions are large, and the differences in plant species and ecological environments lead to large differences in the measurement results of carbon sink capacity.ConclusionThis research provides critical insights into the interplay of factors shaping the carbon sink potential of urban parks, emphasizing the importance of stable foundational strategies like design and maintenance. While habitat composition and planting strategies offer substantial localized benefits, their variability necessitates tailored interventions informed by specific ecological and social contexts. To advance urban carbon neutrality efforts, future research should integrate these findings into practical tools, such as enhanced modules in landscape performance platforms. These modules should allow for lifecycle assessments that account for design, construction, and maintenance phases, thus supporting real-time monitoring and optimization. Additionally, leveraging human-machine collaboration through intelligent workflows can further enhance decision-making by combining real-time data analysis with human expertise. Future research should expand the assessment system for the composite factors influencing the carbon sink capacity of urban park green space, so as to fill the data gaps in the research on carbon sinks of parks under special ecological environments, and further enrich the data used.